Effect of Xuezhikang Therapy on Expression of Pulmonary Hypertension Related miR-638 in Patients With Low HDL-C Levels - Cao, Ruihua; Sun, Tao; Xu, Ruyi; Zheng, Jin; Wang, Hao; Wang, Xiaona; Bai, Yongyi; Ye, Ping (Frontiers in Pharmacology, 2021)
Objective: Low plasma level of high-density lipoprotein cholesterol (HDL-C) associated with poor outcomes in several cardiovascular diseases, including pulmonary arterial hypertension (PAH). Regulation of miR-638 have been proved to be associated with PAH. The aim of this study was to evaluate the expression of miR-638 after Xuezhikang (XZK) therapy in patients with low HDL-C. Methods: Plasma levels of miR-638 were quantified by real-time polymerase chain reactions in 20 patients with PAH and 30 healthy controls. A total of 40 subjects with low HDL-C were assigned to receive an XZK therapy for 6 months. The miR-638 expression profiles were detected in PAH patients, XZK-treated subjects and lovastatin treated pulmonary arterial smooth muscle cells (PA-SMCs). Results: The relative expression level of miR-638 in the plasma was lower in the PAH patients than that in the controls (p < 0.001). An increase of 11.2% from baseline in the HDL-C level was found after XZK therapy (p < 0.001). The relative expression of miR-638 was increased after XZK treatment (p < 0.01). The changes of miR-638 were inversely associated with baseline HDL-C levels. A significantly reduction in miR-638 expression were found in PDGF-BB-treated hPA-SMCs compared to the control cells, and the pre-treatment of the cells with lovastatin significantly re-gain the expression levels in miR-638. Conclusion: In patients with low HDL-C levels, XZK therapy raised the expression of miR-638, suggesting that the potential therapeutic effect of XZK in PAH patients with low serum HDL-C levels deserves further exploration.